Exploration of student environmental attitude through integrated learning of local potential tourist destinations in Central Lombok - Muhammad Syamsussabri; Endang Lasminawati (Jurnal Pijar Mipa, 2023)
This study explores students' environmental attitudes when participating in science learning that applies tools integrated with the local potential of Central Lombok tourist destinations. This research is descriptive. This research was conducted at junior high school MTsN 3 Lombok Tengah. The research subjects were 28 students from one of class VII. The tools used consist of lesson plans, teaching materials, and assessment instruments that integrate the local potential of Central Lombok tourist destinations. The instruments used are interview guidelines with teachers, observation sheets of learning implementation, and environmental attitude questionnaire instruments validated by expert validators. The results of this study indicate that the average value of environmental attitude in each indicator includes; (a) understanding norms about protecting the environment, which obtains a score of 60 which is included in the good category, (b) knowing the environment that must be maintained obtains a score of 50 which is included in the fairly good category, and (c) demonstrating a commitment to protecting the environment obtains a score of 59 which is included in the good category. These results indicate that using learning tools integrated with the local potential of Central Lombok tourist destinations in the sub-material Interaction of Living Things with the environment for class VII can train students' environmental attitudes.